STRATEGI KOMUNIKASI POLITIK TIM PEMENANGAN FACHRORI-SYAFRIL PADA PILKADA 2020 DI PROVINSI JAMBI - Ega Indiana; Irzal Anderson; Dona Sariani (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the political communication strategy of the winning team, the strengths and weaknesses as well as the causes of the low vote acquisition of Fachrori-Syafril in the 2020 simultaneous regional elections in Jambi Province. The method used in this study is a qualitative research method which emphasizes the in-depth aspects of a problem. The results of this study indicate that the political communication strategy used by the Fachrori-Syafril winning team still has problems and obstacles that cause the low vote acquisition for candidate pair number 02 Fachrori-Syafril in the 2020 Simultaneous Regional Head Elections in Jambi Province. This is due to limited campaign factors, new people in the political realm, candidate management does not work and the disappointment factor from the community.